Anti-slip Control for Unmanned Underwater Tracked Bulldozer Based on Active Disturbance Rejection Control. (June 2022) - He, Dingchang; Li, Yong; Meng, Xiangpeng; Si, Qiaorui
Abstract: The unmanned underwater tracked bulldozer (UUTB) plays an essential role in dredging and clearing riverbed obstacles in flood season. The track slip leads to instability and energy consumption while the UUTB sinkage into the soft sediment on the riverbed. The track anti-slip control strategy is proposed based on active disturbance rejection control (ADRC) in this article. An identification strategy of optimal slip rate is investigated by the method of adaptive step coefficient. The motion model of UUTB is established by the RecurDyn environment. The track traction system, anti-slip controller and adaptive slip rate identification strategy are established in the MATLAB/Simulink environment. The ADRC based anti-slip rate control strategy is verified by the co-simulation of RecurDyn and MATLAB/simulink. Two conditions with different slippery ground is established to verify the anti-slip rate control strategy. Simulation and experimental results indicate that the proposed ADRC-based anti-slip rate control strategy can effectively reduce the slip rate and improve the operating stability of the UUTB prototype. The significance of this paper is to alleviate the problem of poor mobility caused by track slipping when the UUTB underwater operation.